PENGATURAN PERLINDUNGAN DATA PRIBADI KONSUMEN JASA KEUANGAN DALAM PENGGUNAAN UANG ELEKTRONIK BERBASIS SERVER - Permana, Sukarelawati (Faculty of Law, Parahyangan Catholic University, 2022)
The digitalization of the economy in Indonesia in the Covid-19 pandemic situation has further encouraged banks and business actors to make innovations in order to reduce direct contact with consumers of financial services, one of which is the presence of server-based electronic money. Users who use these services are required to fill in their personal data first. With the provision of personal data belonging to consumers of financial services or users, the issuer of server-based electronic money has an obligation to protect users' personal data so that unauthorized dissemination or misuse of data does not occur. The widespread use of server-based electronic money in public activities makes provisions related to the protection of personal data important in order to protect users. However, it is necessary to examine whether the provisions on the protection of personal data of financial service consumers on server-based electronic money have met best practices. To answer these problems, research was conducted using normative juridical methods sourced from library materials. The results of the research obtained are the protection of personal data of consumers of financial services on server-based electronic money has been regulated in regulations that aim to protect users' personal data. The regulation has adopted the principles of personal data regulation as well as the General Data Protection Regulation (GDPR) and the existing laws and regulations in Indonesia. These regulations play a role in protecting the rights of users regarding their personal data such as the right to assimilate or withdraw the consent that has been given previously.